IMPACT OF HEALTH INFORMATION EXCHANGE (HIE) ON THE COMPLETENESS AND ACCURACY OF SHARED MEDICAL RECORDS - Fahad Bandar Almutairi, Khulud Masad Almutairi, Sami Sayyaf Alruwaili, Fatimah Jameel Al – Qobaii, Mosa Ahmed Mosa Hashim, Ibtisam Hamdan Almutairi, Saad Dagash Moed Alqahtani, (Chelonian Research Foundation, 2022)
With the increasing number of electronic health records that are interoperable (iEHRs) or health information exchanges (HIEs), there is a growing need and opportunity to evaluate the existing evidence on the effectiveness and limitations of adopting, using, and the impact of iEHRs. The objective of this research is to evaluate the global body of evidence about the implementation, use, and effects of iEHRs. We performed a comprehensive evaluation by searching several databases, including MEDLINE, Embase, and the Cumulative Index to Nursing and Allied Health material (CINAHL), along with additional searches in Google Scholar and sources of unpublished material. This study provides an overview of a dynamic and vibrant subject that examines the use and influence of iEHRs. Although the aggregate results indicate several beneficial effects, the main studies were not rigorously assessed for their quality. When analyzed based on individual measurement criteria, the findings highlighted both consistently good outcomes and mostly negative or inconclusive results. Keywords: health information exchange; electronic health record; interoperability; utilization; influence; systematic review